2015
DOI: 10.1186/s12967-015-0520-2
|View full text |Cite
|
Sign up to set email alerts
|

Notch-1 knockdown suppresses proliferation, migration and metastasis of salivary adenoid cystic carcinoma cells

Abstract: BackgroundNotch-1 promotes invasion and metastasis of cancer cells but its role in salivary adenoid cystic carcinoma (SACC) remains unelucidated. Here, we sought to investigate the effect of Notch-1 knockdown on the invasion and metastasis of SACC cells.MethodsStable ACC-M cells whose Notch-1 was silenced by lentiviral vectors were established. Cellular proliferation was evaluated by the MTT assays and clonogenic assays, apoptosis by flow cytometry and the migration of ACC-M cells by Transwell assays. Metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…At the same time, the Notch signaling pathway was highly activated in adherent lymphoma cells. We therefore concluded that Notch pathway activation correlates with tumor cell proliferation, as shown by previous studies [34, 35]. Regarding chemoresistance, lymphoma cells cultured alone were more sensitive to lymphoma cells from the coculture system, as previous studies indicated [36].…”
Section: Discussionsupporting
confidence: 79%
“…At the same time, the Notch signaling pathway was highly activated in adherent lymphoma cells. We therefore concluded that Notch pathway activation correlates with tumor cell proliferation, as shown by previous studies [34, 35]. Regarding chemoresistance, lymphoma cells cultured alone were more sensitive to lymphoma cells from the coculture system, as previous studies indicated [36].…”
Section: Discussionsupporting
confidence: 79%
“…48 A study by Chen et al focusing on the role of Notch in salivary adenoid cystic carcinoma cells, found that knockdown of Notch-1 significantly inhibited the formation of metastatic lung nodules induced by EMT. 49 While it is unclear how the Notch signaling pathway regulates primary tumor cells disseminating to the lung, we speculate that it may play a critical role in the adaptation of breast cancer cells to metastatic niches. Notch signaling pathway may also interact with other signaling pathways to dictate the function and fate of breast cancer cells during the metastatic process.…”
Section: Notch Signaling Pathwaymentioning
confidence: 84%
“…To metastasize, a cancer cell must acquire abilities such as the capacity to colonize new tissue and evade immune surveillance, which must involve a broad spectrum of mechanisms. Gene expression profiling experiments have uncovered many genes potentially implicated in cancer invasion and metastasis [ 25 28 ]. Matrix metalloproteinases (MMPs), a family of zinc-ion dependent endopeptidases comprising more than 21 subtypes, have been widely accepted to play an important role on cancer invasion or metastasis [ 29 32 ].…”
Section: Discussionmentioning
confidence: 99%